2021
DOI: 10.21203/rs.3.rs-936472/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An In-vitro evaluation of a polyherbal formulation, against SARS-CoV-2

Abstract: Background: COVID-19, caused by SARS-CoV-2 is one of the major health crisis that has affected the world in the past century. With the emergence of new strains of viruses and antimicrobial resistance, the world is looking for an alternate therapeutic option to fight infectious disease.Objective: The present study evaluated the efficacy of a novel polyherbal formulation, named NOQ19, against SARS-CoV-2 in an in vitro setting. NOQ 19 is an unique blend of 13 Ayurvedic herbs.Methodology: Vero E6 (CL1008), the Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Previous studies on the same formulation NOQ19 have shown promising results with respect to rate of recovery and antiviral e cacy [23][24][25] . A review of Ayurvedic literature presents robust preclinical evidence for e cacy of multiple NOQ19 ingredients such as Ashwagandha (Withania somnifera) and Guduchi (Tinospora cordifolia), along with Amalaki (Phyllanthus emblica) in proliferation of B and T cells and activation of nonspeci c immunity 32 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies on the same formulation NOQ19 have shown promising results with respect to rate of recovery and antiviral e cacy [23][24][25] . A review of Ayurvedic literature presents robust preclinical evidence for e cacy of multiple NOQ19 ingredients such as Ashwagandha (Withania somnifera) and Guduchi (Tinospora cordifolia), along with Amalaki (Phyllanthus emblica) in proliferation of B and T cells and activation of nonspeci c immunity 32 .…”
Section: Discussionmentioning
confidence: 98%
“…A previous in vitro study conducted on NOQ19 demonstrated its antiviral e cacy among Vero E6 SARS-CoV-2 infected cell lines. The treatment of virus infected cells with 0.9mg/ml concentration of NOQ19 resulted in a 100% viral elimination 23 . The NOQ19 was further tested in the Syrian golden hamsters animal model.…”
Section: Introductionmentioning
confidence: 99%
“…[31] An Ayurvedic formulation, NOQ19 which contained W. somnifera herb displayed potent antiviral activity against SARS-CoV-2 in Vero E6 cell lines. [56] -…”
Section: Withania Somniferamentioning
confidence: 99%
“…[56] In addition, it has been proven to inhibit viral replication of various types of viruses including the influenza virus. [56] Among the various phytochem-icals, the immunomodulatory effect of cordifolioside A was stronger than berberine due to its interaction with TGF-β and TNF-α receptors. [81] Although its binding affinity to Mpro was quite low, cordifolioside A has high potential in modulating the cytokine storm event in Covid-19 patients.…”
Section: Regulation Of Mpro and Cytokine Stormmentioning
confidence: 99%
“…Piperine plays an important role in inhibiting the entry of SARS-CoV-2 into the cell by increasing the curcumin and catechin in plasma. This role is attributed to the bioavailability enhancement property of piperine [24] . Previous in vitro studies on NF2 have shown 100% antiviral e cacy in a Vero E6 cell line-based assay [25] .…”
Section: Introductionmentioning
confidence: 99%